PERBANDINGAN HUKUM TINDAKAN ABORSI TERHADAP WANITA KORBAN PERKOSAAN MENURUT HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Adinda Nabilla; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The cases of unwanted pregnancy because rape surely burdensome for women, both medically and psychologically, because rape is the imposition of sexual relations with women without any volition of conscious. The problems of abortion can't be seen simply. From a religious side, abortion is expressly stated as a prohibited practice. Not much different from religion, Abortion in morally also valued as an immoral actions. because abortion substantially is nothing more than killing an innocent fetus.The formulation of the problem and the purpose of this essay is to find out how is the comparison of crime of abortion due to rape based on Islamic and the Law of number 36 Year 2009 about Health and also to find out what is the legal protection will be given to women who have abortions due to rape.The type of this essay is normative research. Normative research is a study that discusses about the principles of law, systematics of law, the degree of synchronization of law, history of law, and comparative of law. The method of this essay is legal comparison, that is study law by reviewing more than one legal system to find the similarities and the differences, in order to get the specific conclusions.The conclusion of this essay is Law number 36 of 2009 concerning Health declares that basically abortion is prohibited, however, for cases of abortion due to rape, it is legal as long as still followed the terms of the law. at the same time, according to Islamic law, there are differences of opinion regarding abortion carried out due to rape. Majelis Tarjih Muhammadiyah which forbids abortion due to rape and Majelis Ulama Indonesia which allows abortion due to rape before the fetus is 40 days old. Then, the legal protection given to pregnant women due to rape that aborted their womb is contained in Law of 36 number 2009 concerning Health which allows acts of abortion due to rape as long as these actions is suitable by the procedures in the Act.Keyword: Abortion- Rape- Law Of Islamic- Legal Protection